You are Here: Home >< Maths

# How do I rearrange this ? watch

1. hey guys I have a question

if I have 3x^2 -10x +7 = 0

how do I make x the subject and hence find x ?

first I made it : 3x^2 -10x = -7

but I don't know how to rearrange this algebraically
2. (Original post by kingkongjaffa)
hey guys I have a question

if I have 3x^2 -10x +7 = 0

how do I make x the subject and hence find x ?

first I made it : 3x^2 -10x = -7

but I don't know how to rearrange this algebraically
Quadratic formula or complete the square? (I suggest the former)

Are you aware of those techniques?
3. Basically, simply all that you can in the first step.

3x*2 - 10x +7 = 0 will become
6x -10x +7 = 0, which will become
-4x + 7 = 0, which will become
-4x = -7, so
x = -7/-4, the minuses cancel each other out, so basically,

x= 7/4

Is this the type of simplification that you mean? Or have I misunderstood the point?

Point taken, wrong type of math.

Sorry guys, please don't mind this post!
4. (3x-7)(x-1)= 0...

Then carry on...
5. (Original post by Farhan.Hanif93)
Quadratic formula or complete the square? (I suggest the former)

Are you aware of those techniques?
This

(Original post by Tizmo)
Basically, simply all that you can in the first step.

3x*2 - 10x +7 = 0 will become
6x -10x +7 = 0, which will become
-4x + 7 = 0, which will become
-4x = -7, so
x = -7/-4, the minuses cancel each other out, so basically,

x= 7/4

Is this the type of simplification that you mean?
NOT this :O
6. yes but I didn't think these would be necessary this is a differentiation question. Thanks.
7. Not what Tizmo said!

I'll carry on then...

if the above is true then x=1 or x=7/3
8. (Original post by Tizmo)
Basically, simply all that you can in the first step.

3x*2 - 10x +7 = 0 will become
6x -10x +7 = 0, which will become
-4x + 7 = 0, which will become
-4x = -7, so
x = -7/-4, the minuses cancel each other out, so basically,

x= 7/4

Is this the type of simplification that you mean? Or have I misunderstood the point?
you sir have misread the question that 3x is raised to the power of two not multiplied by 2

3x squared, not 3x*2
9. (Original post by Tizmo)
Basically, simply all that you can in the first step.

3x*2 - 10x +7 = 0 will become
6x -10x +7 = 0, which will become
-4x + 7 = 0, which will become
-4x = -7, so
x = -7/-4, the minuses cancel each other out, so basically,

x= 7/4

Is this the type of simplification that you mean? Or have I misunderstood the point?
Firstly, please don't post full solutions, it's against the way we post help on here.

Secondly, make sure you understand what you're helping with before posted otherwise that could lead to further confusion.

(Original post by birduk)
(3x-7)(x-1)= 0...

Then carry on...
The question asks you to make x the subject first so factorising is not the way to go.
10. (Original post by birduk)
Not what Tizmo said!

I'll carry on then...

if the above is true then x=1 or x=7/3
thanks how do you come to that? I'm not very good at factorising with things that have coefficients of x :P
11. (Original post by kingkongjaffa)
thanks how do you come to that? I'm not very good at factorising with things that have coefficients of x :P
Use the quadratic formula then, it always works!
12. is this for c2? i have a funny feeling i recognise this question and if so its in differentiation and you do have to factorise the quadratic
13. No birduk is right by make the subject i didnt mean in that sense sorry for the confusion.
14. ya it is
15. Sorry guys, totally misread the question!

16. (Original post by Tizmo)
Sorry guys, totally misunderstood the question!

17. (Original post by eliotball)
What I meant to say. Cheers mate.
18. (Original post by kingkongjaffa)
hey guys I have a question

if I have 3x^2 -10x +7 = 0

how do I make x the subject and hence find x ?

first I made it : 3x^2 -10x = -7

but I don't know how to rearrange this algebraically
Factorise...

3x^2-10x +7 = 0

ac = 21

(3x^2 -3x) (-7x + 7)=0

3x(x-1) -7(x -1) = 0

(3x - 7) (x-1) =0

x = 7/3 and x = 1
19. (Original post by Tizmo)
What I meant to say. Cheers mate.
No problem, I'm sure you had good intentions posting that solution, it was just a pretty awful mistake :P
20. (Original post by crazycake93)
Factorise...

3x^2-10x +7 = 0

ac = 21

(3x^2 -3x) (-7x + 7)=0

3x(x-1) -7(x -1) = 0

(3x - 7) (x-1) =0

x = 7/3 and x = 1
ooh can you explain this please firstly AC is 3*7 but can you explain why you did that.
secondly can you explain how you go from 3x(x-1) -7(x-1) to (3x-7) (x-1)?

### Related university courses

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: March 21, 2011
The home of Results and Clearing

### 2,341

people online now

### 1,567,000

students helped last year
Today on TSR

### University open days

1. London Metropolitan University
Sat, 18 Aug '18
2. Edge Hill University
Sat, 18 Aug '18
3. Bournemouth University
Sat, 18 Aug '18
Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams